Direct Thrombin Inhibition in Extracorporeal Membrane Oxygenation. Issue 7 (July 2022) - Geli, Janos; Capoccia, Massimo; Maybauer, Dirk M.; Maybauer, Marc O.
Extracorporeal membrane oxygenation (ECMO) is a widely used technique to provide circulatory and/or respiratory support in critically ill patients. ECMO treatment usually necessitates systemic anticoagulation. Unfractionated Heparin (UFH) is a commonly used anticoagulant in patients on ECMO support. In situations where UFH is contraindicated, alternative anticoagulation strategies can be applied, such as the use of direct thrombin inhibitors (DTI). Bivalirudin and argatroban are the most widely used DTIs. In this report we give account of the current evidence regarding dosing, monitoring and complications associated with the use of these agents in ECMO dependent patients.